Voltage-gated calcium channel currents in human coronary myocytes. Regulation by cyclic GMP and nitric oxide. - Quignard, J F (1997)
Voltage-gated Ca2+ channels contribute to the maintenance of contractile tone in vascular myocytes and are potential targets for vasodilating agents. There is no information available about their nature and regulation in human coronary arteries. We used the whole-cell voltage-clamp technique to characterize Ca2+-channel currents immediately after enzymatic dissociation and after primary culture of coronary myocytes taken from heart transplant patients. We recorded a dihydropyridine-sensitive L-type current in both freshly isolated and primary cultured cells. A T-type current was recorded only in culture. The L- (but not the T-) type current was inhibited by permeable analogues of cGMP in a dose-dependent manner. This effect was mimicked by the nitric oxide-generating agents S-nitroso-N-acetylpenicillamine (SNAP) and 3-morpholinosydnonimine which increased intracellular cGMP. Methylene blue, known to inhibit guanylate cyclase, antagonized the effect of SNAP. Inhibitions by SNAP and cGMP were not additive and seemed to occur through a common pathway. We conclude that (a) L-type Ca2+ channels are the major pathway for voltage-gated Ca2+ entry in human coronary myocytes; (b) their inhibition by agents stimulating nitric oxide and/or intracellular cGMP production is expected to contribute to vasorelaxation and may be involved in the therapeutic effect of nitrovasodilators; and (c) the expression of T-type Ca2+ channels in culture may be triggered by cell proliferation.